Diversity and host assemblage of avian haemosporidians in different terrestrial ecoregions of Peru. Issue 1 (1st April 2021) - Garcia-Longoria, Luz; Muriel, Jaime; Magallanes, Sergio; Villa-Galarce, Zaira Hellen; Ricopa, Leonila; Inga-Díaz, Wilson Giancarlo; Fong, Esteban; Vecco, Daniel; Guerra-SaldaÑa, César; Salas-Rengifo, Teresa; Flores-Saavedra, Wendy; Espinoza, Kathya; et al.
Abstract: Characterizing the diversity and structure of host–parasite communities is crucial to understanding their eco-evolutionary dynamics. Malaria and related haemosporidian parasites are responsible for fitness loss and mortality in bird species worldwide. However, despite exhibiting the greatest ornithological biodiversity, avian haemosporidians from Neotropical regions are quite unexplored. Here, we analyze the genetic diversity of bird haemosporidian parasites ( Plasmodium and Haemoproteus ) in 1, 336 individuals belonging to 206 bird species to explore for differences in diversity of parasite lineages and bird species across 5 well-differentiated Peruvian ecoregions. We detected 70 different haemosporidian lineages infecting 74 bird species. We showed that 25 out of the 70 haplotypes had not been previously recorded. Moreover, we also identified 81 new host–parasite interactions representing new host records for these haemosporidian parasites. Our outcomes revealed that the effective diversity (as well as the richness, abundance, and Shannon–Weaver index) for both birds and parasite lineages was higher in Amazon basin ecoregions. Furthermore, we also showed that ecoregions with greater diversity of bird species also had high parasite richness, hence suggesting that host community is crucial in explaining parasite richness. Generalist parasites were found in ecoregions with lower bird diversity, implying that the abundance and richness of hosts may shape the exploitation strategy followed by haemosporidian parasites. These outcomes reveal that Neotropical region is a major reservoir of unidentified haemosporidian lineages. Further studies analyzing host distribution and specificity of these parasites in the tropics will provide important knowledge about phylogenetic relationships, phylogeography, and patterns of evolution and distribution of haemosporidian parasites.